2016
DOI: 10.1038/ejhg.2016.155
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up care by a genetic counsellor for relatives at risk for cardiomyopathies is cost-saving and well-appreciated: a randomised comparison

Abstract: Increasing numbers of patient relatives at risk of developing dilated or hypertrophic cardiomyopathy (DCM/HCM) are being identified and followed up by cardiologists according to the ACC/ESC guidelines. However, given limited healthcare resources, good-quality low-cost alternative approaches are needed. Therefore, we have compared conventional follow-up by a cardiologist with that provided at a cardiogenetic clinic (CGC) led by a genetic counsellor. Phenotype-negative first-degree relatives at risk for DCM/HCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“… 30 , 31 Follow-up contacts by healthcare professionals with the proband (and relatives carrying the familial variant) regarding informing at-risk relatives may also improve uptake, since barriers regarding informing relatives can be discussed and support can be offered to overcome them. 30 32 Considering the uptake over time, particularly the steep declining rate after the first year, follow-up contacts should ideally take place after 2 months and again after 1 or 2 years following disclosure of the test result to the proband, for example, as proposed in the study of Nieuwhof et al 33 that describes a cardiogenetic follow-up clinic. Unfortunately, limited research has been performed on how effective interventions are in improving family communication.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Follow-up contacts by healthcare professionals with the proband (and relatives carrying the familial variant) regarding informing at-risk relatives may also improve uptake, since barriers regarding informing relatives can be discussed and support can be offered to overcome them. 30 32 Considering the uptake over time, particularly the steep declining rate after the first year, follow-up contacts should ideally take place after 2 months and again after 1 or 2 years following disclosure of the test result to the proband, for example, as proposed in the study of Nieuwhof et al 33 that describes a cardiogenetic follow-up clinic. Unfortunately, limited research has been performed on how effective interventions are in improving family communication.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies (3,954 individuals) reported on the uptake of genetic counseling, which was delivered by a variety of healthcare providers, including genetic counselors, cardiologists, and nurses (Table 1). The uptake of genetic counseling ranged from 37% to 68% in probands (Hudson et al, 2019; Khouzam et al, 2015; Otten et al, 2015) and 38%–84% in at‐risk relatives (Christiaans et al, 2008; Helio et al, 2020; Nieuwhof et al, 2017; van den Heuvel et al, 2020). Uptake of genetic counseling did not differ when counseling was provided by a genetic counselor/nurse versus a cardiologist (Nieuwhof et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of genetic counseling did not differ when counseling was provided by a genetic counselor/nurse versus a cardiologist (Nieuwhof et al, 2017). Finally, uptake of genetic counseling for pediatric patients was 56% (Christiaans et al, 2008;van den Heuvel et al, 2020).…”
Section: Uptake Of Genetic Counselingmentioning
confidence: 94%
See 1 more Smart Citation
“…The lack of a pathogenic or likely pathogenic variant does not rule out a genetic cause, as variants in genes not known to cause DCM may be present; in this situation, the patients should inform their first-degree family members, and those family members should undergo clinical screening for DCM every three to five years. Genetic counselors represent a critical resource for providing this information to patients [32].…”
Section: Importance Of Genetic Counselingmentioning
confidence: 99%